Advancements in sorption-enhanced steam reforming for clean hydrogen production: A comprehensive review - Ahmad Salam Farooqi; Abdelwahab N. Allam; Muhammad Zubair Shahid; Anas Aqil; Kevin Fajri; Sunhwa Park; Omar Y. Abdelaziz; Mahmoud M. Abdelnaby; Mohammad M. Hossain; Mohamed A. Habib; Syed Muhammad Wajahat ul Hasnain; Ali Nabavi; et al. (Carbon Capture Science & Technology)
The sorption-enhanced steam methane reforming (SE-SMR) process, which integrates methane steam reforming with in situ CO2 capture, represents a breakthrough technology for clean hydrogen production. This comprehensive review thoroughly explores the SE-SMR process, highlighting its ability to efficiently combine carbon capture with hydrogen generation. The review evaluates the mechanisms of SE-SMR and evaluates a range of innovative sorbent materials, such as CaO-based, alkali-ceramic, hydrotalcite, and waste-derived sorbents. The role of catalysts in enhancing hydrogen production within SE-SMR processes is also discussed, with a focus on bi-functional materials. In addition to examining reaction kinetics and advanced process configurations, this review touches on the techno-economic aspects of SE-SMR. While the analysis does not provide an in-depth economic evaluation, key factors such as potential capital costs (CAPEX), operational expenses (OPEX), and scalability are considered. The review outlines the potential of SE-SMR to offer more efficient hydrogen production, with the added benefit of in situ carbon capture simplifying the process design. Although a detailed economic comparison with other hydrogen production technologies was not the focus, this review emphasizes SE-SMR's promise as a scalable and flexible solution for clean energy. With its integrated design, SE-SMR offers pathways to industrial-scale hydrogen production. This review serves as a valuable resource for researchers, policymakers, and industry experts committed to advancing sustainable and efficient hydrogen production technologies.